2017
DOI: 10.1002/jbio.201600198
|View full text |Cite
|
Sign up to set email alerts
|

Optomechanical measurement of the role of lamins in whole cell deformability

Abstract: There is mounting evidence that the nuclear envelope, and particularly the lamina, plays a critical role in the mechanical and regulation properties of the cell and changes to the lamina can have implications for the physical properties of the whole cell. In this study we demonstrate that the optical stretcher can measure changes in the time-dependent mechanical properties of living cells with different levels of A-type lamin expression. Results from the optical stretcher shows a decrease in the deformability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…The increase of laser power induces a cell stretching, revealing the time-dependent mechanical response of the cell. This tool has been recently used by Kolb et al [ 65 ] to probe the nuclear properties of both adult mouse fibroblasts (adherent cell line) and K562 cells (suspension cell line) with different nuclear lamin A levels. Authors demonstrated that, in physiological conditions, the nucleus deforms less than the surrounding cytoskeleton.…”
Section: Mechanical Characterization Techniquesmentioning
confidence: 99%
“…The increase of laser power induces a cell stretching, revealing the time-dependent mechanical response of the cell. This tool has been recently used by Kolb et al [ 65 ] to probe the nuclear properties of both adult mouse fibroblasts (adherent cell line) and K562 cells (suspension cell line) with different nuclear lamin A levels. Authors demonstrated that, in physiological conditions, the nucleus deforms less than the surrounding cytoskeleton.…”
Section: Mechanical Characterization Techniquesmentioning
confidence: 99%